Hollow gradient‑structured iron‑anchored carbon nanospheres for enhanced electromagnetic wave absorption - Wu, Cao (2023)
In the present paper, a microwave absorber with nanoscale gradient structure was proposed for enhancing the electromagnetic absorption performance. The inorganic–organic competitive coating strategy was employed, which can effectively adjust the thermodynamic and kinetic reactions of iron ions during the solvothermal process. As a result, Fe nanoparticles can be gradually decreased from the inner side to the surface across the hollow carbon shell. The results reveal that it offers an outstanding refection loss value in combination with broadband wave absorption and flexible adjustment ability, which is superior to other relative graded distribution structures and satisfied with the requirements of lightweight equipment. In addition, this work elucidates the intrinsic microwave regulation mechanism of the multiscale hybrid electromagnetic wave absorber. The excellent impedance matching and moderate dielectric parameters are exhibited to be the dominative factors for the promotion of microwave absorption performance of the optimized materials. This strategy to prepare gradient-distributed microwave absorbing materials initiates a new way for designing and fabricating wave absorber with excellent impedance matching property in practical applications.